Linguistically Intercultural Problems in Learning English as a Global Lingua Franca (EGLF) - Diemroh Ihsan (LINGUA: Jurnal Bahasa dan Sastra, 2018)
Abstract: In learning English as a Lingua Franca (ELF) of the globe, Indonesian learners of English as a Foreign Language (EFL) need great effort and seriousness to cope with certain linguistic and incultural problems. If beginning EFL learners make errors in making sentences using certain words, it is not surprising but it is when they are made by quite advanced learn- ers. However, errors should be respected and accepted as signs of learning as no learners create errors on purpose. Teachers should realize that errors are committed due to some factors that are beyond learners’ awareness linguistically as well as culturally. This paper is intended to describe some linguistic and incultural errors made by advanced EFL learners and discuss some possible causes and offer ways to help them improve their competence and performance in the English language. The data used in this study are in forms of (a) sentences made by 30 Mag- ister program students using certain words given, and (b) answers they provide based on Yes/ No questions and Tag-questions asked. The study reveals that to make correct sentences using certain words and correct answers to certain questions in English EFL learners are required to build some linguistic, pragmatic, and intercultural comptence both in Indonesian and English.Keywords: linguistic, pragmatic, and intercultural errors and competence,Abstrak: Dalam belajar bahasa Inggris sebagai bahasa perantara antar bangsa di dunia para siswa Indonesia yang belajar bahasa Inggris sbagai bahasa asng memerlukan usaha yang sung- guh-sungguh untuk memahami dan menguasai unsur-unsur kebahasaan dan kebudayaan tert- entu. Jika pembelajar pemula bahasa Inggris Indonesia membuat kesalahan dalam membuat kalimat dengan menggunakan kata-kata tertentu, itu mungkin dianggap wajar tetapi hal tersebut dianggap kurang wajar bila kesalahan seperti itu dibuat oleh pembelajar yang sudah dikategori- kan kelas advanced. Namun demikian, kesalahan apapun yang dibuat pembelajar hendaknya dihargai dan diterima sebagai tanda bahwa mereka sedang belajar karena tidak ada pembelajar yang sengaja membuat kesalahan apabila mereka sudah mengetahui mana yang benar. Para guru harus menyadari bahwa kesalahan terjadi karena beberapa faktor di luar pemahaman pem- belajar baik secara kebahasaan maupun budaya. Tulisan ini mencoba mendeskripsikan beber- apa unsur kebahasaan dan budaya yang dibuat oleh pembelajar bahasa Inggris sebagai bahasa asing, membahas beberapa penyebabnya, dan menawarkan beberapa usaha untuk membantu mereka memperbaiki pengetahuan dan kemampuan berbahasa Inggris mereka. Data penelitian ini berupa (a) sejumlah kalimat yang dibuat oleh 30 orang pembelajar S2 bahasa Inggris, dan(b) kalimat jawaban yang mereka buat berdasarkan pertanyaan Yes/No Question dan Tag-Ques- tion. Hasil studi ini menyatakan bahwa untuk dapat membuat kalimat yang benar dan jawaban dari pertanyaan Yes/No Question dan Tag-Question para pembelajar bahasa Inggris Indonesia dituntut untuk memiliki latarbelakang pengetahuan tentang ilmu bahasa, pragmatik, dan bu- daya sendiri maupun budaya bangsa yang berbahasa Inggris.Kata-kata Kunci: kesalahan dan kemampuan linguistik, pragmatik, interkultural